Asupan Dobel Protein Hewani Berhubungan Dengan Pencegahan Risiko Stunting Pada Anak Usia 13-24 Bulan - Sastriani Sastriani; Eva Yuliani; Sastrariah Sastrariah; Eunike Arruan M (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2026)
Stunting is a condition of growth failure in children due to chronic malnutrition and is stated to have a short length or height compared to children of their age, which results in delayed child growth. One of the factors that can cause growth retardation in children under five is the lack of intake of nutrients such as protein. Efforts to double animal protein in complementary foods can provide many good benefits for children's growth period. This study aims to determine the relationship between animal double protein intake and the risk of stunting in children aged 13-24 months in the working area of the Sendana 1 Health Center. This type of research is using quantitative methods, with a Retrospective Cohort design, using an analytical observational approach. Pollution is all children aged 13-24 months in Tallu Banua Village, sample sampling technique with total sampling, data collection using a 24-hour food recall questionnaire. The intake of animal protein double in the respondents did not differ much (low 55.3% and high 44.7%). The results of the chi-square test obtained a p=value value of 0.001 which means that there is a significant relationship between double protein intake and stunting events. Based on the results of the study, there was a significant relationship between children who did not consume double animal protein and the risk of stunting in children aged 13-24 months in the working area of the Sendana 1 health center. Mothers should be able to increase the intake of various types of animal protein by utilizing local foods sourced from side dishes so that children avoid stunting.